2016
DOI: 10.1007/s10877-016-9855-3
|View full text |Cite
|
Sign up to set email alerts
|

High veno-arterial carbon dioxide gradient is not predictive of worst outcome after an elective cardiac surgery: a retrospective cohort study

Abstract: Alteration of tissue perfusion is a main contributor of organ dysfunction. In cardiac surgery, the importance of organ dysfunction is associated with worse outcome. Central venous-arterial difference in CO tension (ΔCO) has been proposed as a global marker of the adequacy of tissue perfusion in shock states. We hypothesized that ΔCO could be increased in case of postoperative organ failure or worse outcome. In this monocentric retrospective cohort study, we retrieved, from our database, 220 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
2
16
0
5
Order By: Relevance
“…Although many studies confirmed the association between an elevation in both ∆PCO 2 and ∆PCO 2 /C a-v O 2 ratio and poor outcome in terms of lactate clearance, changes in VO 2 and mortality (40)(41)(42), some other ones showed a limited or even a negative correlation between elevated ∆PCO 2 and increase in blood lactate or mortality (43)(44)(45). Part of the discrepancy might be related to the fact that the latter studies were performed in post-cardiac surgery patients.…”
Section: Errors and Pitfalls Of The Pco 2 Gapmentioning
confidence: 99%
“…Although many studies confirmed the association between an elevation in both ∆PCO 2 and ∆PCO 2 /C a-v O 2 ratio and poor outcome in terms of lactate clearance, changes in VO 2 and mortality (40)(41)(42), some other ones showed a limited or even a negative correlation between elevated ∆PCO 2 and increase in blood lactate or mortality (43)(44)(45). Part of the discrepancy might be related to the fact that the latter studies were performed in post-cardiac surgery patients.…”
Section: Errors and Pitfalls Of The Pco 2 Gapmentioning
confidence: 99%
“…Our findings agree with other studies that showed a weak correlation between Pv-aCO2 difference with some physiologic parameters like CI, pH, Hb, BE, SvO2, etc. (29,30). Moreover, it has been shown that this variable was not able to detect significant changes in systemic blood flow, and global O2 derived metabolism following goal-directed therapy, (1) or after fluid challenges in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Robin's study, this gradient was significantly different between complicated and non-complicated patients at admission in intensive care unit, but tended to subsequently decrease. In the Morel's [4] study, the number of patients having a high gradient was greater at 6th postoperative hour. It is likely that the circulatory management brought into play to the high risk patients may rapidly modify the gradient whereas the tissue insult induced by the microvascular disorder is still an ongoing process.…”
mentioning
confidence: 88%
“…In this issue Morel et al [4] retrospectively analysed 220 consecutive patients admitted in intensive care unit after an elective cardiac surgery. Monitoring p(mv-a)CO 2 , they observed at the 6th postoperative hour a group of 55 patients having a gradient greater than 6 mm Hg.…”
mentioning
confidence: 99%